PEA GRAINS IN DRYING: UNRAVELING THE KINETICS OF HOT-AIR DRYING AND EXPLORING MATHEMATICAL MODELS FOR MOISTURE DIFFUSION - Doymaz, Ibrahim; Acarali, Nil (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2024)
Pea drying studies were assessed to learn more about the kinetics and properties of drying in a hot-air dryer. Research was done on impact of temperatures and pre-treatments on drying behaviours. The drying rate graphs demonstrated that the entire drying procedure took place when rates were declining. To properly understand the experimental data, four mathematical models (Henderson & Pabis, Page, Wang & Singh, and Aghbashlo et al.) were used. The Page model was discovered to be the ideal one to depict peas' curves of drying. The identification of the Page model as the most suitable for depicting pea drying curves underscored the applicability in modeling drying behaviors in similar agricultural products. With Fick's second law of diffusion, effective moisture diffusivity (Deff) sorted from 2.45x10-10 to 6.55x10-10 m2/s at given temperature. D eff was expressed as a function of temperature with an Arrhenius type equation. For samples from Potas, Blanch, and Control codes, the activation energy for moisture diffusion was computed as 21.48, 22.82, and 22.32 kJ/mol, respectively. The computation of activation energy for moisture diffusion for different samples offered practical information for optimizing drying processes under various conditions. The results showed the importance of pea drying kinetics and practical implications for industry on drying efficiency and product quality.
Keywords: Drying kinetics; pea; effective moisture diffusivity; Page model; GREEN PEAS; OPTIMIZATION; SELECTION; Thermodynamics; Engineering